Long-term Clinical Results of Vitrectomy and Scleral Buckling in Treatment of Rhegmatogenous Retinal Detachment - I. Schmidt; N. Plange; G. Rößler; H. Schellhase; A. Koutsonas; P. Walter; B. Mazinani (The Scientific World Journal)
Purpose. Most studies about retinal detachment cover a limited follow-up period. The purpose of this research is to assess the long-term results after pars plana vitrectomy (PPV) and scleral buckle (SB) surgery in patients with rhegmatogenous retinal detachment (RRD). Methods. 155 patients with RRD are treated either with SB or PPV with a mean follow-up of more than 5 years. Retrospective analysis of patient data with RRD was performed between January 2006 and June 2008 at a tertiary eye clinic. Results. Overall primary success rate was 85.2% (PPV: 84.6%, SB: 89.5%; p=0.57). 90.5% of redetachments appeared within the first 124 days. No significant different success rate was found for vitrectomy with and without additional encircling band (p=0.09). No advantage of a supplemental encircling band in cases of preoperative inferior breaks was seen (p=0.81). Patients of SB group were treated more frequently in follow-up time because of epiretinal membrane (ERM) (SB: 15.5% versus PPV: 7.3%). No patient of the PPV group without intraoperative use of endolaser cerclage (14.7%) had any peeling surgery postoperatively. Conclusion. Redetachment rates of both methods are comparable in a clinical setting where PPV is considered a suitable method for pseudophakic patients and in complex cases and SB was performed in younger phakic patients with clearly identified retinal tears. PPV seems to show a more heterogenous pattern of complications. No advantage of a supplemental encircling band could be found in these case series of patients with primary RRD. No relevant long-term risk of redetachment was seen after SB.